Dimeria anandibaiana (Poaceae: Panicoideae): a new species from Konkan region of Maharashtra, India - Paithane, V. A.; Bhuktar, A. S.; Chorghe, A. R.; Gosavi, K. V. C.; Kashetti, R. P.; Patil, S. B. (Phytotaxa, 2024)
Dimeria anandibaiana, a new species of Poaceae, is described and illustrated from the Konkan region of Maharashtra. The new species is morphologically allied to D. stapfiana C. E. Hubb. ex. Pilg. A detailed description of the new species, along with a comparative analysis of allied species, coloured photographs, illustration, distribution, and ecological notes, are provided in this paper.